A standardized inspection methodology to evaluate municipal solid waste collection performance. (15th September 2019) - Calabrò, Paolo S.; Komilis, Dimitrios
Abstract: The success of separate collection of municipal solid waste, the efficiency of the other connected services and the justification of a large cost assumed by an authority, depends on the level of service provided to customers as well as the citizens' attitude towards waste management. In this paper, a semi-qualitative inspection method to evaluate both the door-to-door collection system and the conventional curbside system is proposed. The method is based on the combined evaluation of waste collection using a set of indicators and the assessment of the perception of the citizens towards collection and street cleaning services using behavioural questionnaires. The ultimate goal was to assess potential differences between door-to-door and curbside collection systems. The standardized inspection evaluation method was applied to the city of Reggio, Calabria (Italy), since both collection systems are used there. The standardized inspection evaluation proved to be simple to implement and was effective to accurately evaluate the quality of the service delivered to the citizens. The results of the behavioural survey revealed that citizens that practised door-to-door separation had a higher recycling conscience and were more satisfied with the city waste management system than the ones that practised curbside separation. According to the results of the study, there was a qualitative agreement between the results of the standardized inspection evaluation and the behavioural survey. The door to door collection system is suggested to replace the curbside collection system. Highlights: The new method of standardized inspection evaluation (SIE) was proposed and applied. SIE method was effective to accurately evaluate the quality of the service delivered. Recycling behaviour was not considerably associated to gender, age and education. SIE results qualitatively agree with the behavioural survey results.